Purification and molecular cloning of an inducible gram-negative bacteria-binding protein from the silkworm, Bombyx mori. - Lee, W J (1996)
A 50-kDa hemolymph protein, having strong affinity to the cell wall of Gram(-) bacteria, was purified from the hemolymph of the silkworm, Bombyx mori. The cDNA encoding this Gram(-) bacteria-binding protein (GNBP) was isolated from an immunized silkworm fat body cDNA library and sequenced. Comparison of the deduced amino acid sequence with known sequences revealed that GNBP contained a region displaying significant homology to the putative catalytic region of a group of bacterial beta-1,3 glucanases and beta-1,3-1,4 glucanases. Silkworm GNBP was also shown to have amino acid sequence similarity to the vertebrate lipopolysaccharide receptor CD14 and was recognized specifically by a polygonal anti-CD14 antibody. Northern blot analysis showed that GNBP was constitutively expressed in fat body, as well as in cuticular epithelial cells of naive silkworms. Intense transcription was, however, rapidly induced following a cuticular or hemoceolien bacterial challenge. An mRNA that hybridized with GNBP cDNA was also found in the l(2)mbn immunocompetent Drosophila cell line. These observations suggest that GNBP is an inducible acute phase protein implicated in the immune response of the silkworm and perhaps other insects.